Actitudes homofóbicas en estudiantes universitarios de Psicopedagogía y Psicología Educativa - Ortega Gualli, Gabriela Alexandra (2021)
The objective of this research was to determine the attitudes of the students of the Psychopedagogy and Educational Psychology career towards Homosexuality to estimate its prevalence within the school context in which they develop and to contrast the homophobic attitudes of university men and women. The sample consisted of 98 students distributed by semesters. The methodology had a quantitative approach, the design was non-experimental, the type of research was descriptive and correlational by level or scope. The instrument for data collection was the Attitudes Scale Test towards lesbians and homosexual men (ATLG), which consisted of 20 items, 10 to measure the attitude towards homosexual men and 10 to measure the attitude towards lesbians in turn by four dimensions condemnation-acceptance and denial of any similarity between homosexual and heterosexual relationships, feelings of repulsion or threat towards homosexual people. It concluded that there were subtle attitudes of homophobia in university students which justified by their religious beliefs or by the social context of the study population, however, it revealed that there was a percentage of students who showed an indifferent attitude towards homophobia who neither approve nor reject it, just as there were students who indicate acceptance towards sexual diversity.